Evaluation of the Implementation of the Job Order Costing Method in the Traditional Gamelan Craft of Mustika Laras - Rizka, Arya Novan Nur; Umarella, Barus; Ardiansyah, Ardiansyah (Jurnal Ekualisasi, 2026)
This study evaluates the implementation of the job order costing method in traditional crafts. The originality of the research lies in the detailed mapping of production costs using job order costing in traditional culture-based handicraft businesses, which are still relatively limited in previous research. The purpose of this study is to evaluate the implementation of job order costing in determining the cost of production. The research method used is field research with a qualitative descriptive approach. Primary and secondary data were collected through observation, limited interviews, and documentation with data on the production and sales of traditional crafts in this case gamelan. Empirical results show that gamelan sales in the 2022–2024 period have decreased due to weakening buyer interest due to sluggish economic conditions. However, sales revenue is still greater than production costs, so the business does not suffer losses. Profit planning analysis shows that by 2025 businesses must sell at least eight sets of gamelan to achieve a profit target of 20%. The implications of this study show that the implementation of job order costing can help MSMEs in improving the accuracy of profit planning, cost control, and business sustainability.